SINERGISITAS PEMERINTAH DAERAH DAN PEMERINTAH PUSAT DALAM PENGEMBANGAN WISATA TAMAN NASIONAL BUKIT TIGAPULUH DI KABUPATEN INDRGAIRI HULU TAHUN 2013-2015 - Handaka, Gagah Adia; Wicaksono, Baskoro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
For optimizing the development of Bukit Tigapuluh National Park, the Central Government synergizes with the Regional Government in maintaining, developing and protecting the Bukit Tigapuluh National Park area. It is important for the Central Government to synergize with the Local Government in maintaining the development of Bukit Tigapuluh National Park area to prevent the misuse of the area, from the result of the research, it is known that the synergicity between the two parties is still overlapping, hence the writer tries to see and develop the synergy between the Central Government and Local Government. The purpose of this study is to optimize the synergy between the Central Government and the Local Government so that supervision in the development of Bukit Tigapuluh National Park can be maintained and reduce the level of criminality inside and outside the region in order to maintain the forest stability covering the phalura and fauna. The type of research used is qualitative research method. The location of this research was conducted at Bukit Tigapuluh National Park (TNBT) of Indragiri Hulu Regency. Data collection techniques are done by completing the information through interviews and doing documentation requesting the necessary data to the agency to be investigated. While the data analysis is done using qualitative analysis method. Based on the results of the study the authors draw the conclusion that the synergism that occurred in the development of Bukit Tigapuluh National Park is not yet running optimally, especially from the private sector that minimal information about the condition around the area. The security of the area also still requires more strict guarding by the addition of Forest Police personnel, so that events such as illegal logging and poaching of endangered species can be minimized to the safest point of Bukit Tigapuluh National Park area. Keywords: Synergy, Tourism Development, Government